Toxic shock a social history - Vostral, Sharra Louise, 1968- (New York University, 2018)
In 1980, young, healthy women in the United States suddenly began to get sick and even die. The unexpected link to these deaths was superabsorbent tampons. Thousands of women used them during their menstrual periods, signaling the potential for a large-scale outbreak. 'Toxic Shock' traces the emergence of this new illness of toxic shock syndrome (TSS) and its relationship to tampon technology. This multifaceted history engages microbiology, design and innovation, journalism and mass communication, product liability, and federal policy and regulation. The broad scope captures the various approaches that contributed to defining meaning about the emergent illness.